Modularly-assembled light-cured waterborne woodware emulsion coating and preparation method thereof
The photocured aqueous wood emulsion coating is prepared by modular assembly method, which solves the problems of unstable performance and high cost caused by inconsistent synthetic modification methods in the prior art, and achieves efficient and stable coating curing and excellent paint film performance.
Patent Information
- Application Number
- CN202510035668.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The existing synthetic and modification methods for photocuring water-based wood coatings are not uniform, resulting in unstable product performance and high cost.
The photocured aqueous wood emulsion coating is prepared by modular assembly method. By preparing core-shell latex particles and Pickering emulsion, the intermolecular action force is enhanced, the emulsion stability is improved, and the coating curing speed is improved through the synergistic effect of functionalized latex particles and photocured oil phase.
The good universality and stability of photocured water-based wood emulsion coatings are achieved, which significantly improves the coating curing speed, improves the paint film performance, and reduces production costs.
Smart Images

Figure CN119823602A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water-based wood emulsion coatings, and in particular relates to a modular assembly light-curing water-based wood emulsion coating and a preparation method thereof. Background Art
[0002] Artificial boards are mostly used for interior decoration such as furniture, floors, and walls. In order to improve the characteristics of artificial boards and make them more suitable for industrial production, protect wood from environmental factors and improve the appearance quality of products, wood coatings need to be applied on the surface of artificial boards. Solvent-based wood coatings use organic solvents as diluents. Although these coatings dry quickly and have good gloss, they have the problem of volatile organic compound emissions. With the enhancement of people's environmental awareness and the improvement of national laws and regulations, water-based wood coatings have become a hot topic in the current research of wood coatings due to their advantages such as being green and environmentally friendly and not producing volatile organic compounds.
[0003] However, water-based wood coatings use water as solvent, which has a slow evaporation rate and a long film-forming time. During use, multiple coatings are required to achieve good performance. Various reasons lead to low coating efficiency of water-based wood coatings, which greatly limits its application and promotion. Photocurable water-based wood coatings are currently an important means to improve the drying speed of water-based coatings. The commonly used preparation method is to introduce monomers with photocurable groups into water-based resins.
[0004] Monomers with photocurable groups are usually hydrophobic, while water-based resins are hydrophilic, so the compatibility between monomers and water-based resins needs to be solved through synthetic modification. The chemical properties of different monomers with photocurable groups and water-based resins vary greatly. For example, some monomers may contain functional groups that are easily hydrolyzed or oxidized, while water-based resins may have specific functional groups or molecular structures. This difference in chemical properties requires specific design and adjustment for specific monomers and resins during the modification process, making it difficult to form a universal modification method.
[0005] Due to the diversity of modification methods, light-cured waterborne wood coatings produced by different manufacturers or different batches may have large differences in performance, resulting in instability and waste of product performance. In addition, since different modification methods may require different raw materials and equipment, it will also increase production costs and complexity. Summary of the invention
[0006] In order to solve the problem that the existing synthesis and modification methods of light-curing water-based wood coatings are not unified, resulting in unstable product performance and high cost, the present invention provides a modular assembly light-curing water-based wood emulsion coating and a preparation method thereof.
[0007] The technical solution of the present invention:
[0008] A method for modularly assembling a light-curing water-based wood emulsion coating comprises the following steps:
[0009] Step 1: Preparation of core-shell latex particles:
[0010] S1: Prepare the following raw materials in parts by mass: 110-165 parts of deionized water, 50-80 parts of core monomer, 20-50 parts of shell monomer 1, 0.6-1.2 parts of grafting monomer, 6-12 parts of composite emulsifier, 0.2-0.5 parts of initiator and 0.3-0.6 parts of pH buffer;
[0011] S2: dissolving 0.12-0.3 parts of initiator in 5.5-8 parts of deionized water to prepare a first initiator solution; dissolving 0.08-0.2 parts of initiator in 9.5-13 parts of deionized water to prepare a second initiator solution;
[0012] S3: Mix the remaining deionized water, composite emulsifier and pH buffer, stir and pre-emulsify, then heat to 60°C, continue stirring for a certain period of time, add 8 to 12.8 parts of core layer monomer and first initiator solution, continue stirring for a certain period of time, then heat to 65°C, and when the reaction system solution turns milky blue and the reflux of the condenser disappears, a seed emulsion is obtained;
[0013] S4: raising the temperature of the obtained seed emulsion to 80° C., reducing the stirring speed, dropping the remaining 42 to 67.2 parts of the core layer monomer into the seed emulsion, and adding the second initiator solution;
[0014] S5: After the core layer monomer is added dropwise, the temperature is kept for a certain period of time, and the grafting monomer is added dropwise; after the grafting monomer is added, the shell layer monomer 1 is added dropwise immediately, and after the shell layer monomer 1 is fully added, the temperature is kept for a certain period of time, and the material is cooled to room temperature and discharged to obtain a core-shell latex particle emulsion; the core-shell latex particle emulsion is centrifuged and purified to collect the core-shell latex particles;
[0015] Step 2: Assemble the Pickering emulsion:
[0016] SⅠ: Prepare the following raw materials in parts by weight: 10-60 parts of deionized water, 10-50 parts of core-shell latex particles, 10-50 parts of photocurable oil phase reagent, 1-5 parts of photoinitiator, 0.5-1.2 parts of sodium magnesium lithium silicate, 0.16-0.32 parts of tannic acid and 1-5 parts of emulsifier;
[0017] SⅡ: dissolving the emulsifier in deionized water to prepare an emulsion with a concentration of 1%, and dissolving tannic acid in the remaining deionized water to prepare a tannic acid solution;
[0018] SⅢ: Add tannic acid solution to the core-shell latex particles, stir for 0.5-1.5h, then add sodium magnesium lithium silicate, vortex mix to ensure that the core-shell latex particles are tightly coated by the complex formed by tannic acid and sodium magnesium lithium silicate, centrifuge to remove excess complex, and obtain a functionalized emulsion;
[0019] SⅣ: The obtained functionalized emulsion and the obtained emulsion are evenly mixed as the water phase, the photocurable oil phase reagent and the photoinitiator are evenly mixed as the oil phase, the oil phase is added dropwise to the water phase at a dispersion speed of 4000-6000 rpm, and the Pickering emulsion is assembled after sufficient dispersion to obtain a photocurable water-based wood emulsion coating.
[0020] Furthermore, the core layer unit is vinyl acetate, the shell layer monomer 1 is styrene, the graft monomer is maleic anhydride, the composite emulsifier is an equal mass mixture of PCA507 and PCA078, the initiator is ammonium persulfate, the pH buffer is sodium bicarbonate, the photocurable oil phase reagent is a monomer or polymer containing acrylate double bonds, a monomer or polymer containing methacrylate double bonds, a monomer or polymer containing vinyl ether double bonds, a polymer containing allyl double bonds, a polymer containing other C=C double bonds or a double bond-modified vegetable oil; the photoinitiator is 2-hydroxy-1-methylpropiophenone, and the emulsifier is sodium dodecyl sulfate, OP-10 or epoxy polyether polyol emulsifier.
[0021] Furthermore, the monomer or polymer containing acrylate double bonds includes methyl acrylate, ethyl acrylate or acrylate type epoxy resin; the monomer or polymer containing methacrylate double bonds includes 2-methyl methacrylate, glycidyl methacrylate or polymethyl methacrylate; the monomer or polymer containing vinyl ether double bonds includes monovinyl ether, polyvinyl ether, vinyl ether type epoxy resin; the polymer containing allyl double bonds includes polyisoprene or allyl resin; the polymer containing other C=C double bonds includes alkyd resin; the double bond modified vegetable oil includes soybean oil, castor oil, linseed oil or tung oil modified with acrylate double bonds.
[0022] Furthermore, the pre-emulsification temperature in step 1 S3 is 25-60°C, the stirring speed of the pre-emulsification is 200-600rpm, and the stirring time is 5-30min; the temperature is raised to 60°C after pre-emulsification and the stirring time is continued for 10-35min, and the stirring time after adding the core layer monomer and the first initiator solution is continued for 10-40min.
[0023] Furthermore, in step 1 S4, the stirring speed of the seed emulsion is 200-500 rpm, the dropping speed of the core layer monomer is 0.3-0.6 mL / min, and the second initiator solution is added 30 minutes after the core layer monomer is added, and the dropping speed is 0.1-0.3 mL / min.
[0024] Furthermore, in step 1 S5, after the core layer monomer is added, the insulation time is 5 to 30 minutes, the dripping speed of the grafted monomer is 0.5 to 3 mL / min, the dripping speed of the shell layer monomer 1 is 0.5 to 2 mL / min, and after 3 to 15 minutes of dripping, it is adjusted to 0.1 to 1 mL / min until all the shell layer monomer 1 is added. After all the shell layer monomer 1 is added, the insulation time is 20 to 40 minutes.
[0025] Furthermore, in step 1 S5, after all the shell monomer 1 is added dropwise and kept warm for 30 minutes, shell monomer 2 is added at a dropping rate of 0.5 mL / min. After all the addition is completed, it is kept warm for 30 minutes, cooled to room temperature and discharged to obtain a double-bond functionalized core-shell latex particle emulsion, which is then centrifuged and purified to obtain double-bond functionalized core-shell latex particles.
[0026] Furthermore, the shell monomer 2 is dipentene.
[0027] Furthermore, the method further comprises step 3, preparing a photocurable composite emulsion: adding the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 and stirring evenly, and the obtained photocurable composite emulsion is the photocurable water-based wood emulsion coating.
[0028] Furthermore, the mass ratio of the pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 1:9 to 5:5.
[0029] A light-curing water-based wood emulsion coating prepared by a method for modularly assembling a light-curing water-based wood emulsion coating provided by the invention.
[0030] Beneficial effects of the present invention:
[0031] The modular assembly method for preparing a light-curing water-based wood emulsion coating provided by the present invention has good universality, can effectively introduce different oil-soluble substances into water-based coatings, and can enhance the intermolecular forces through modular assembly, thereby effectively improving the stability of the emulsion. In order to further broaden the application field, the modular composite emulsion constructed with double-bond functionalized latex particles as stable particles of the present invention also has good stability, and through the synergistic effect of functionalized latex particles and light-curing oil phase, the curing speed of the coating is greatly improved, and the performance of the paint film is significantly improved.
[0032] The photocurable water-based wood emulsion coating prepared by the present invention exhibits an excellent photocuring speed when used on the surface of a board and the surface of a wood product with a primer. The curing can be completed in 20 seconds on the surface of an ordinary board, and the fastest curing can be achieved in 31 seconds when applied to the surface of a wood product with a primer, which significantly improves the coating efficiency of the water-based emulsion coating and broadens the application range of the water-based photocurable coating.
[0033] The present invention has a simple process for preparing a light-curing water-based wood emulsion coating by modular assembly, the reaction conditions are easy to control, and the cost is low. The performance of the prepared wood paint film can meet the use requirements, and water is used as a solvent, which is environmentally friendly and can alleviate environmental pollution problems. It has broad development prospects in the field of water-based wood coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The infrared spectra of the PVAc / PS latex films obtained by different methods in Experimental Example 1; (1) is a latex film made of Pickering emulsion assembled from functionalized PVAc / PS emulsion in Example 1; (2) is a latex film made of Pickering emulsion assembled from functionalized PVAc / PS emulsion prepared by blending only with tannic acid in Comparative Example 2; (3) is a latex film made of Pickering emulsion assembled from pure PVAc / PS emulsion in Comparative Example 1;
[0035] Figure 2 TEM image of the functionalized PVAc / PS latex particles prepared in step 2 SⅢ of Example 1;
[0036] Figure 3 is the SEM image of the polystyrene Pickering emulsion particles in Experimental Example 2;
[0037] Figure 4 A comparison chart of the photocuring time of the photocurable waterborne wood latex coatings prepared in Examples 1 to 6;
[0038] Figure 5 This is a photo of the photocurable water-based wood latex coatings prepared in Examples 1 to 6 after curing;
[0039] Figure 6 A comparison chart of the photocuring time of the secondary coating of the photocurable waterborne wood emulsion coating prepared in Examples 1 to 6;
[0040] Figure 7 This is a physical picture of the light-curable water-based wood latex coating prepared in Examples 1 to 6 after secondary coating and curing;
[0041] Figure 8 The infrared spectra of double bond functionalized latex particles PVAc / Ps-Limonene and pure PVAc / PS latex particles prepared in Example 7;
[0042] Fig. 9 This is a comparison chart of the photocuring time of the photocurable waterborne wood latex coatings prepared in Examples 7 to 12;
[0043] Fig.10This is a photo of the photocurable water-based wood latex coatings prepared in Examples 7 to 12 after curing;
[0044] Fig.11 A comparison chart of the photocuring time of the secondary coating of the photocurable waterborne wood emulsion coating prepared in Examples 7 to 12;
[0045] Fig.12 This is a real picture of the light-curable water-based wood emulsion coating prepared in Example 7-Example 2 after secondary coating and curing. DETAILED DESCRIPTION
[0046] The technical solution of the present invention is further described below in conjunction with the embodiments, but it is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention shall be included in the protection scope of the present invention. The process equipment or devices not specifically noted in the following embodiments are all conventional equipment or devices in the art. If not specifically specified, the raw materials used in the embodiments of the present invention can be obtained commercially; if not specifically specified, the technical means used in the embodiments of the present invention are all conventional means well known to those skilled in the art.
[0047] Example 1
[0048] This embodiment provides a method for modularly assembling a light-curing water-based wood emulsion coating, comprising the following steps:
[0049] Step 1: Preparation of core-shell latex particles:
[0050] S1: Prepare the following raw materials in parts by weight: 140 parts of deionized water, 70 parts of core monomer vinyl acetate, 30 parts of shell monomer 1 styrene, 1.0 parts of graft monomer maleic anhydride, 10 parts of composite emulsifier, 0.35 parts of initiator ammonium persulfate and 0.5 parts of pH buffer sodium bicarbonate; wherein the composite emulsifier is a mixture of equal weights of PCA507 and PCA078;
[0051] S2: dissolving 0.25 parts of the initiator in 7.5 parts of deionized water to prepare a first initiator solution; dissolving 0.1 parts of the initiator in 12.5 parts of deionized water to prepare a second initiator solution;
[0052] S3: The remaining deionized water, composite emulsifier and pH buffer are mixed, stirred at 300 rpm for pre-emulsification at 30°C for 10 minutes, and then the temperature is raised to 60°C. After stirring for 20 minutes, 10 parts of core layer monomer and the first initiator solution are added, and the temperature is raised to 65°C after stirring for 20 minutes. When the reaction system solution turns milky blue and the reflux of the condenser disappears, the seed emulsion is obtained;
[0053] S4: The temperature of the reaction system was raised to 80°C, the stirring rate was reduced to 250 rpm, and the remaining 60 parts of the core layer monomer were added dropwise to the obtained seed emulsion at a dropping speed of 0.4 mL / min. After 30 minutes of dropping, the second initiator solution was added to the system at a dropping speed of 0.1 mL / min;
[0054] S5: After the core layer monomer is added, keep warm for 10 minutes and add the graft monomer at a dropping speed of 1.0 mL / min; immediately after the graft monomer is added, add the shell layer monomer 1 at a dropping speed of 0.8 mL / min. After 4 minutes, adjust the dropping speed to 0.3 mL / min until all the shell layer monomer 1 is added, keep warm for 30 minutes, cool to room temperature and discharge to obtain PVAc / PS core-shell latex particle emulsion; centrifuge and purify the core-shell latex particle emulsion, remove the precipitate and supernatant, take the stable part of the middle layer, and ensure that the latex particle size of the subsequent assembly of the two-phase particles is uniform.
[0055] Step 2: Assemble the Pickering emulsion:
[0056] SⅠ: Prepare the following raw materials in parts by weight: 35 parts of deionized water, 25 parts of core-shell latex particles, 40 parts of photocurable oil phase reagent vinyl acetate, 3 parts of photoinitiator 2-hydroxy-1-methylpropiophenone, 0.6 parts of sodium magnesium lithium silicate, 0.24 parts of tannic acid and 3 parts of emulsifier sodium dodecyl sulfate;
[0057] SⅡ: dissolving the emulsifier in deionized water to prepare an emulsion with a concentration of 1%, and dissolving tannic acid in the remaining deionized water to prepare a tannic acid solution;
[0058] SⅢ: Add tannic acid solution to the core-shell latex particles, stir for 1 hour, then add sodium magnesium lithium silicate, vortex for 2 minutes to mix well to ensure that the core-shell latex particles are tightly coated by the complex formed by tannic acid and sodium magnesium lithium silicate, and remove the excess complex by centrifugation to obtain the functionalized PVAc / PS emulsion;
[0059] SⅣ: The obtained functionalized PVAc / PS emulsion and the obtained emulsion are evenly mixed as the water phase, the photocurable oil phase reagent and the photoinitiator are evenly mixed as the oil phase, and the oil phase is added dropwise to the water phase at a dispersion speed of 5000 rpm. After all the addition is completed, continue to disperse for 3 minutes to complete the assembly of the Pickering emulsion and obtain a photocurable water-based wood emulsion coating.
[0060] Example 2
[0061] The difference between this embodiment and embodiment 1 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step three, preparing a light-curing composite emulsion:
[0062] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 1:9. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0063] Example 3
[0064] The difference between this embodiment and embodiment 1 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step three, preparing a light-curing composite emulsion:
[0065] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 2:8. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0066] Example 4
[0067] The difference between this embodiment and embodiment 1 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step three, preparing a light-curing composite emulsion:
[0068] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 3:7. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0069] Example 5
[0070] The difference between this embodiment and embodiment 1 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step three, preparing a light-curing composite emulsion:
[0071] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 4:6. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0072] Example 6
[0073] The difference between this embodiment and embodiment 1 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step three, preparing a light-curing composite emulsion:
[0074] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 5:5. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0075] Example 7
[0076] This embodiment provides a method for modularly assembling a light-curing water-based wood emulsion coating, comprising the following steps:
[0077] Step 1: Preparation of core-shell latex particles:
[0078] S1: Prepare the following raw materials in parts by weight: 140 parts of deionized water, 70 parts of core monomer vinyl acetate, 30 parts of shell monomer 1 styrene, 1.0 parts of graft monomer maleic anhydride, 10 parts of composite emulsifier, 0.35 parts of initiator ammonium persulfate and 0.5 parts of pH buffer sodium bicarbonate; wherein the composite emulsifier is a mixture of equal weights of PCA507 and PCA078;
[0079] S2: dissolving 0.25 parts of the initiator in 7.5 parts of deionized water to prepare a first initiator solution; dissolving 0.1 parts of the initiator in 12.5 parts of deionized water to prepare a second initiator solution;
[0080] S3: The remaining deionized water, composite emulsifier and pH buffer are mixed, stirred at 300 rpm for pre-emulsification at 30°C for 10 minutes, and then the temperature is raised to 60°C. After stirring for 20 minutes, 10 parts of core layer monomer and the first initiator solution are added, and the temperature is raised to 65°C after stirring for 20 minutes. When the reaction system solution turns milky blue and the reflux of the condenser disappears, the seed emulsion is obtained;
[0081] S4: The temperature of the reaction system was raised to 80°C, the stirring rate was reduced to 250 rpm, and the remaining 60 parts of the core layer monomer were added dropwise to the obtained seed emulsion at a dropping speed of 0.4 mL / min. After 30 minutes of dropping, the second initiator solution was added to the system at a dropping speed of 0.1 mL / min;
[0082] S5: After the core layer monomer is added dropwise, keep warm for 10 minutes, and add the graft monomer at a dropping speed of 1.0 mL / min; immediately after the graft monomer is added, add the shell layer monomer 1 at a dropping speed of 0.8 mL / min. After 4 minutes, adjust the dropping speed to 0.3 mL / min until all the shell layer monomer 1 is added, keep warm for 30 minutes, add the shell layer monomer 2 at a dropping speed of 0.5 mL / min, keep warm for 30 minutes after all the addition is completed, cool to room temperature and discharge to obtain a double-bond functionalized PVAc / PS core-shell latex particle emulsion; centrifuge and purify the core-shell latex particle emulsion, remove the precipitate and supernatant, take the stable part of the intermediate layer, and ensure that the latex particle size of the subsequent assembly of the two-phase particles is uniform.
[0083] Step 2: Assemble the Pickering emulsion:
[0084] SⅠ: Prepare the following raw materials in parts by weight: 35 parts of deionized water, 25 parts of core-shell latex particles, 40 parts of photocurable oil phase reagent vinyl acetate, 3 parts of photoinitiator 2-hydroxy-1-methylpropiophenone, 0.6 parts of sodium magnesium lithium silicate, 0.24 parts of tannic acid and 3 parts of emulsifier sodium dodecyl sulfate;
[0085] SⅡ: dissolving the emulsifier in deionized water to prepare an emulsion with a concentration of 1%, and dissolving tannic acid in the remaining deionized water to prepare a tannic acid solution;
[0086] SⅢ: Add tannic acid solution to the core-shell latex particles, stir for 1 hour, then add sodium magnesium lithium silicate, vortex for 2 minutes to mix well to ensure that the core-shell latex particles are tightly coated by the complex formed by tannic acid and sodium magnesium lithium silicate, and remove the excess complex by centrifugation to obtain the functionalized PVAc / PS emulsion;
[0087] SⅣ: The obtained functionalized PVAc / PS emulsion and the obtained emulsion are evenly mixed as the water phase, the photocurable oil phase reagent and the photoinitiator are evenly mixed as the oil phase, and the oil phase is added dropwise to the water phase at a dispersion speed of 5000 rpm. After all the addition is completed, the dispersion is continued for 3 minutes to complete the assembly of the Pickering emulsion and obtain a double-bond functionalized photocurable water-based wood emulsion coating.
[0088] Example 8
[0089] The difference between this embodiment and embodiment 7 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step 3, preparing a light-curing composite emulsion:
[0090] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 1:9. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0091] Example 9
[0092] The difference between this embodiment and embodiment 7 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step 3, preparing a light-curing composite emulsion:
[0093] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 2:8. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0094] Example 10
[0095] The difference between this embodiment and embodiment 7 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step 3, preparing a light-curing composite emulsion:
[0096] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 3:7. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0097] Embodiment 11
[0098] The difference between this embodiment and embodiment 7 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step 3, preparing a light-curing composite emulsion:
[0099] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 4:6. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0100] Example 12
[0101] The difference between this embodiment and embodiment 7 is that the method for preparing the modular assembly light-curing water-based wood latex coating in this embodiment further includes step 3, preparing a light-curing composite emulsion:
[0102] The mass ratio of the Pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 5:5. The Pickering emulsion is added to the core-shell latex particle emulsion and stirred evenly. The obtained photocurable composite emulsion is the photocurable waterborne wood emulsion coating.
[0103] Comparative Example 1
[0104] The difference between this comparative example and Example 1 is that pure PVAc / PS emulsion that has not been treated with tannic acid and sodium magnesium lithium silicate is used when assembling the Pickering emulsion in this comparative example. The specific preparation steps are as follows:
[0105] Step 1: Preparation of core-shell latex particles:
[0106] S1: Prepare the following raw materials in parts by weight: 140 parts of deionized water, 70 parts of core monomer vinyl acetate, 30 parts of shell monomer 1 styrene, 1.0 parts of graft monomer maleic anhydride, 10 parts of composite emulsifier, 0.35 parts of initiator ammonium persulfate and 0.5 parts of pH buffer sodium bicarbonate; wherein the composite emulsifier is a mixture of equal weights of PCA507 and PCA078;
[0107] S2: dissolving 0.25 parts of the initiator in 7.5 parts of deionized water to prepare a first initiator solution; dissolving 0.1 parts of the initiator in 12.5 parts of deionized water to prepare a second initiator solution;
[0108] S3: The remaining deionized water, composite emulsifier and pH buffer are mixed, stirred at 300 rpm for pre-emulsification at 30°C for 10 minutes, and then the temperature is raised to 60°C. After stirring for 20 minutes, 10 parts of core layer monomer and the first initiator solution are added, and the temperature is raised to 65°C after stirring for 20 minutes. When the reaction system solution turns milky blue and the reflux of the condenser disappears, the seed emulsion is obtained;
[0109] S4: The temperature of the reaction system was raised to 80°C, the stirring rate was reduced to 250 rpm, and the remaining 60 parts of the core layer monomer were added dropwise to the obtained seed emulsion at a dropping speed of 0.4 mL / min. After 30 minutes of dropping, the second initiator solution was added to the system at a dropping speed of 0.1 mL / min;
[0110] S5: After the core layer monomer is added, keep warm for 10 minutes and add the graft monomer at a dropping speed of 1.0 mL / min; immediately after the graft monomer is added, add the shell layer monomer 1 at a dropping speed of 0.8 mL / min. After 4 minutes, adjust the dropping speed to 0.3 mL / min until all the shell layer monomer 1 is added, keep warm for 30 minutes, cool to room temperature and discharge to obtain PVAc / PS core-shell latex particle emulsion; centrifuge and purify the core-shell latex particle emulsion, remove the precipitate and supernatant, take the stable part of the middle layer, and ensure that the latex particle size of the subsequent assembly of the two-phase particles is uniform.
[0111] Step 2: Assemble the Pickering emulsion:
[0112] SⅠ: Prepare the following raw materials in parts by weight: 35 parts of deionized water, 25 parts of core-shell latex particles, 40 parts of photocurable oil phase reagent vinyl acetate, 3 parts of photoinitiator 2-hydroxy-1-methylpropiophenone and 3 parts of emulsifier sodium dodecyl sulfate;
[0113] SⅡ: dissolve the emulsifier in deionized water to prepare an emulsion with a concentration of 1%;
[0114] SⅢ: The core-shell latex particles, emulsion and core-shell latex particles are mixed evenly to obtain PVAc / PS emulsion as the water phase, the photocurable oil phase reagent and the photoinitiator are mixed evenly as the oil phase, and the oil phase is added dropwise to the water phase at a dispersion speed of 5000 rpm. After all the addition is completed, the dispersion is continued for 3 minutes to complete the assembly of the Pickering emulsion and obtain the photocurable water-based wood emulsion coating.
[0115] Comparative Example 2
[0116] The difference between this comparative example and Example 1 is that the functionalized PVAc / PS emulsion treated with tannic acid is used when assembling the Pickering emulsion in this comparative example. The specific preparation steps are as follows:
[0117] Step 1: Preparation of core-shell latex particles:
[0118] S1: Prepare the following raw materials in parts by weight: 140 parts of deionized water, 70 parts of core monomer vinyl acetate, 30 parts of shell monomer 1 styrene, 1.0 parts of graft monomer maleic anhydride, 10 parts of composite emulsifier, 0.35 parts of initiator ammonium persulfate and 0.5 parts of pH buffer sodium bicarbonate; wherein the composite emulsifier is a mixture of equal weights of PCA507 and PCA078;
[0119] S2: dissolving 0.25 parts of the initiator in 7.5 parts of deionized water to prepare a first initiator solution; dissolving 0.1 parts of the initiator in 12.5 parts of deionized water to prepare a second initiator solution;
[0120] S3: The remaining deionized water, composite emulsifier and pH buffer are mixed, stirred at 300 rpm for pre-emulsification at 30°C for 10 minutes, and then the temperature is raised to 60°C. After stirring for 20 minutes, 10 parts of core layer monomer and the first initiator solution are added, and the temperature is raised to 65°C after stirring for 20 minutes. When the reaction system solution turns milky blue and the reflux of the condenser disappears, the seed emulsion is obtained;
[0121] S4: The temperature of the reaction system was raised to 80°C, the stirring rate was reduced to 250 rpm, and the remaining 60 parts of the core layer monomer were added dropwise to the obtained seed emulsion at a dropping speed of 0.4 mL / min. After 30 minutes of dropping, the second initiator solution was added to the system at a dropping speed of 0.1 mL / min;
[0122] S5: After the core layer monomer is added, keep warm for 10 minutes and add the graft monomer at a dropping speed of 1.0 mL / min; immediately after the graft monomer is added, add the shell layer monomer 1 at a dropping speed of 0.8 mL / min. After 4 minutes, adjust the dropping speed to 0.3 mL / min until all the shell layer monomer 1 is added, keep warm for 30 minutes, cool to room temperature and discharge to obtain PVAc / PS core-shell latex particle emulsion; centrifuge and purify the core-shell latex particle emulsion, remove the precipitate and supernatant, take the stable part of the middle layer, and ensure that the latex particle size of the subsequent assembly of the two-phase particles is uniform.
[0123] Step 2: Assemble the Pickering emulsion:
[0124] SⅠ: Prepare the following raw materials in parts by weight: 35 parts of deionized water, 25 parts of core-shell latex particles, 40 parts of photocurable oil phase reagent vinyl acetate, 3 parts of photoinitiator 2-hydroxy-1-methylpropiophenone, 0.24 parts of tannic acid and 3 parts of emulsifier sodium dodecyl sulfate;
[0125] SⅡ: dissolving the emulsifier in deionized water to prepare an emulsion with a concentration of 1%, and dissolving tannic acid in the remaining deionized water to prepare a tannic acid solution;
[0126] SⅢ: Add tannic acid solution to the core-shell latex particles, stir for 1 hour and then centrifuge to remove excess tannic acid to obtain functionalized PVAc / PS emulsion;
[0127] SⅣ: The obtained functionalized PVAc / PS emulsion and the obtained emulsion are evenly mixed as the water phase, the photocurable oil phase reagent and the photoinitiator are evenly mixed as the oil phase, and the oil phase is added dropwise to the water phase at a dispersion speed of 5000 rpm. After all the addition is completed, continue to disperse for 3 minutes to complete the assembly of the Pickering emulsion and obtain a photocurable water-based wood emulsion coating.
[0128] Emulsion coating effect verification test:
[0129] Test Example 1
[0130] In this test example, latex films were prepared using the Pickering emulsions prepared in Example 1, Comparative Example 1 and Comparative Example 2 as raw materials, and infrared spectra of the latex films obtained by different preparation methods were examined.
[0131] The specific preparation method of the latex film is as follows: 2 g of Pickering emulsion prepared in Example 1, Comparative Example 1 and Comparative Example 2 are respectively placed in a 60 mm × 20 mm × 20 mm silicone mold, and allowed to stand in an oven at 30 ° C for 24 h until completely dried to obtain the latex film required for the test. The infrared spectra of the three different latex films are detected, and the results are as follows: Figure 1 shown.
[0132] Figure 1 The infrared spectra of PVAc / PS latex films obtained by different methods; (1) is a latex film made of Pickering emulsion assembled from functionalized PVAc / PS emulsion in Example 1; (2) is a latex film made of Pickering emulsion assembled from functionalized PVAc / PS emulsion prepared by blending only with tannic acid in Comparative Example 2; (3) is a latex film made of Pickering emulsion assembled from pure PVAc / PS emulsion not treated with tannic acid and sodium magnesium lithium silicate in Comparative Example 1.
[0133] All spectra at 1728 cm -1 A high-intensity C=O stretching vibration absorption peak appears at 1230cm -1 、1025cm -1 There are two obvious COC stretching vibration absorption peaks with different peak intensities; at 2925cm -1 -CH- stretching vibration absorption peak appears at 1369cm -1 Characteristic absorption peaks of -CH3 in-plane bending vibration appear at the core-shell emulsion; these characteristic absorption peaks constitute the characteristic absorption bands of vinyl acetate (VAc), proving the presence of polyvinyl acetate (PVAc) in the core-shell emulsion.
[0134] Further observation revealed that at 3030cm -1 There is a -CH stretching vibration absorption peak on the benzene ring skeleton at 1426cm -1 、1465cm -1 、1524cm -1 、1605cm -1 The C=C vibration absorption peak on the benzene ring appears at 698cm -1 、875cm -1 The out-of-plane bending absorption vibration peak of the monosubstituted -CH on the benzene ring skeleton appears at 1065 cm. These characteristic absorption peaks constitute the characteristic absorption band of styrene (St), which can indicate the presence of polystyrene (PS) in the latex film. At the same time, no characteristic absorption peak of the five-membered ring of the grafted monomer maleic anhydride (MA) was found at 1065 cm -1 It appears at , indicating that MA and PVAc undergo ring-opening polymerization during the reaction to form a 1,4-maleic acid structure, thereby forming a shell monomer grafting site.
[0135] The above analysis shows that PVAc / PS latex particles are polymers composed of PVAc, MA and PS. The infrared spectra of latex films treated by three different methods are roughly the same. By comparing (2) and (3), it can be seen that the latex film prepared by blending with tannic acid (TA) has a peak at 3360 cm -1There is a tiny sharp absorption peak at the 40° point, which is the characteristic absorption peak of phenolic hydroxyl group, but this characteristic absorption peak does not appear in the infrared spectrum of pure PVAc / PS emulsion.
[0136] Comparing (1) and (2), we can see that the phenolic hydroxyl absorption peak appears at 3500 cm -1 The originally sharp and weak phenolic hydroxyl absorption peak becomes broadened. This is because the metal ions (Mg 2+ ) will react with the phenolic hydroxyl group to form a coordination bond between the phenolic hydroxyl group and the magnesium ion, and the two are in an associated state. This can preliminarily prove the success of the latex particle surface functionalization.
[0137] This test example also examines the microstructural characterization of the functionalized PVAc / PS latex particles prepared in Example 1. Figure 2 This is a TEM image of the functionalized PVAc / PS latex particles prepared in step 2 SⅢ of Example 1; it can be seen from the figure that sodium magnesium lithium silicate containing metal cations is added to the system together with tannic acid to form a metal phenol complex network on the surface of the latex particles, so that the metal phenol complex coating can still be stably adsorbed on the surface of the latex particles after ultrasonic purification. The metal phenol complex functionalized coating is evenly coated on the surface of the latex particles, and there is no adhesion between the functionalized latex particles, maintaining good dispersibility, which plays a necessary and favorable condition for the subsequent assembly to form superstructure particles. Combined with the above characterization results, the success of the functionalization of the latex particles can be proved.
[0138] Test Example 2
[0139] This test example investigated the microscopic morphology of Pickering emulsion particles.
[0140] Due to the special property of the photocurable oil phase reagent in Example 1 that the curing reaction is initiated by light, the original morphology of the Pickering emulsion cannot be completely maintained, and it is difficult to directly observe the morphology of the Pickering emulsion particles. Therefore, in this test example, styrene (St) and thermal initiator azobisisobutyronitrile (AIBN) are used to replace the photocurable oil phase reagent and photoinitiator in Example 1 respectively to assemble the Pickering emulsion, and the specific method is as follows:
[0141] The functionalized PVAc / PS emulsion prepared in Example 1 was uniformly mixed with the emulsion as the water phase, St and AIBN were mixed as the oil phase, and the oil phase was added dropwise to the water phase at a dispersion speed of 5000 rpm. After all the addition was completed, the dispersion was continued for 3 minutes to complete the assembly of the Pickering emulsion, and then degassed with nitrogen for 10 minutes, reacted at 65°C for 24 hours, and the styrene in the oil phase was polymerized into polystyrene under the action of the thermal initiator AIBN, which can ensure the morphological integrity of the Pickering emulsion during the drying process. The prepared polystyrene Pickering emulsion was cooled to room temperature and then sampled. The structure of the Pickering emulsion was observed by SEM. The results are as follows: Figure 3 shown.
[0142] Figure 3 It shows that a large number of latex particles are attached to the surface of modularly assembled polystyrene microspheres, indicating that the functionalized latex particles are stabilized on the surface of the emulsion droplets, which is beneficial to enhancing the stability of the droplets.
[0143] Test Example 3
[0144] This test example tests the light-curing time and the properties of the paint film after curing of the light-curing water-based wood emulsion coatings prepared in Examples 1 to 6.
[0145] The light-curable water-based wood latex coatings prepared in Examples 1 to 6 were respectively coated on the surface of the board, and the ultraviolet light wavelength was 395nm and the irradiation distance was 15cm for light curing. The results are as follows Figure 4 As shown in the figure, when the amount of Pickering emulsion added is 10%, the composite emulsion is cured in 58s under ultraviolet light. As the amount of Pickering emulsion added increases, the light curing time is shortened. When the amount added reaches 50%, it takes only 40s to complete the curing, and the curing rate is increased by 31%, indicating that the prepared composite emulsion has good light curing performance.
[0146] Figure 5 This is a photo of the photocurable water-based wood emulsion coatings prepared in Examples 1 to 6 applied once on a wood surface. The paint film properties were tested, and the results are shown in Table 1.
[0147] Table 1
[0148]
[0149] As shown in Table 1, with the increase of the amount of Pickering emulsion added, the glossiness of the paint film formed by the composite emulsion gradually increases, the roughness gradually decreases, the pencil hardness shows an increasing trend, and the adhesion of the emulsion is level 0, which can be well attached to the wood surface. When the amount of Pickering emulsion added is 50%, the performance of the paint film formed is optimal, at this time the adhesion is level 0, the glossiness reaches 31.45, the roughness is reduced to 1.37μm, and the pencil hardness is 2H. Compared with the board coated with pure PVAc / PS emulsion, all properties are improved.
[0150] Test Example 4
[0151] In order to further improve the paint film performance on the surface of the board after photocuring, the board was subjected to a secondary coating of the photocurable water-based wood emulsion coating prepared in Examples 1 to 6 based on the single coating in Test Example 4, and the photocuring time of the secondary coating was tested. The ultraviolet light wavelength was 395 nm and the irradiation distance was 15 cm.
[0152] Figure 6 The test results of the light curing time of the second coating. When the Pickering emulsion addition amount is 10%, the composite emulsion is cured in 73 seconds under ultraviolet light. As the amount of Pickering emulsion added increases, the light curing time is shortened. When the addition amount reaches 50%, it takes only 51 seconds to complete the curing, and the curing rate is increased by 30%. Since the surface of the board has been modified by the emulsion during the first coating, the moisture cannot evaporate through the pores of the board itself. The light curing time of the second coating is slightly increased compared to the first coating, but it can still be cured into a film on the surface of the board relatively quickly.
[0153] Figure 7 This is a photo of the photocurable water-based wood emulsion coatings prepared in Examples 1 to 6 applied twice on a wood surface. The paint film properties were tested, and the results are shown in Table 2.
[0154] Table 2
[0155]
[0156] As shown in Table 2, as the amount of Pickering emulsion added increases, the glossiness of the paint film formed by the composite emulsion gradually increases, the roughness gradually decreases, the pencil hardness tends to increase, and the adhesion of the emulsion is level 0, which can be well attached to the wood surface. When the amount of Pickering emulsion added is 50%, the performance of the paint film formed is optimal. At this time, the adhesion is level 0, the glossiness reaches 36.40, the roughness is reduced to 0.43μm, and the pencil hardness is 3H. Compared with the board coated with pure PVAc / PS emulsion, all performances are improved. Compared with the paint film formed by one coating, the performance is also improved, which can meet the basic use needs.
[0157] Test Example 5
[0158] In order to further improve the photocuring speed of the latex, the latex particles were modified with double bonds functionalization. The PVAc / PS latex particles were grafted with two double bonds with different activities in dipentene, where the more active vinyl double bonds can participate in the polymerization of the latex particle shell layer during the emulsion polymerization process, while the less active cyclohexene structure can be retained in the shell layer, thereby constructing a core-shell structure latex particle with a surface containing photocrosslinkable double bonds.
[0159] Figure 8 The infrared spectra of double-bond functionalized latex particles and pure PVAc / PS latex particles prepared in Example 7; compared with PVAc / PS latex particles, the double-bond functionalized latex particles have an infrared spectrum of 1620 cm -1 An obvious C=C vibration absorption peak appears at , indicating that the double bonds in the added dipentene are retained on the shell layer of the latex particles, and the double-bond functionalized latex particles are successfully synthesized.
[0160] Test Example 6
[0161] This test example tests the light-curing time and the properties of the paint film after curing of the light-curing water-based wood emulsion coatings prepared in Examples 7 to 12.
[0162] The light-curable water-based wood latex coatings prepared in Examples 7 to 12 were respectively coated on the surface of the board, and the UV light wavelength was 395 nm and the irradiation distance was 15 cm for light curing. The results are as follows: Fig. 9 As shown. Due to the low activity of the double bonds retained on the surface of the latex particles in dipentene, the double bond functionalized emulsion cross-links and cures to form a film under ultraviolet light for 48 seconds. When the Pickering emulsion addition amount is 10%, the composite emulsion is cured in 37 seconds under ultraviolet light, and the photocuring rate is increased by 23%. As the amount of Pickering emulsion added increases, the photocuring time is shortened. When the addition amount reaches 50%, it only takes 20.6 seconds to complete the curing, and the curing rate is increased by 57%. The Pickering emulsion has a good synergistic effect with the photocurable latex particles, and the probability of double bond collision cross-linking increases. The obtained photocurable composite emulsion has good photocuring performance.
[0163] Fig.10 This is a photo of the photocurable water-based wood emulsion coatings prepared in Examples 7 to 12 applied once on a wood surface. The paint film properties were tested, and the results are shown in Table 3.
[0164] Table 3
[0165]
[0166] As shown in Table 3, with the increase of the amount of Pickering emulsion added, the glossiness of the paint film formed by the composite emulsion gradually increases, the roughness gradually decreases, the pencil hardness shows an increasing trend, and the adhesion of the emulsion is level 0, which can be well attached to the wood surface. When the amount of Pickering emulsion added is 50%, the performance of the paint film formed is optimal, at this time the adhesion is level 0, the glossiness reaches 27.54, the roughness is reduced to 1.17μm, and the pencil hardness is 3H. Compared with the board coated with pure double bond functionalized emulsion, all properties are improved.
[0167] Test Example 7
[0168] In order to further improve the paint film performance on the surface of the board after photocuring, the board was subjected to a secondary coating of the photocurable water-based wood emulsion coating prepared in Examples 7 to 12 based on the single coating in Test Example 6, and the photocuring time of the secondary coating was tested. The ultraviolet light wavelength was 395 nm and the irradiation distance was 15 cm.
[0169] Fig.11 The results of the photocuring time test for the secondary coating are shown in Figure 2. The double-bond functionalized emulsion without Pickering emulsion was cured in 62 seconds after the secondary coating. When the Pickering emulsion was added at a rate of 10%, the composite emulsion was cured in 51 seconds under ultraviolet light, and the curing rate increased by 17.7%. As the amount of Pickering emulsion added increased, the photocuring time was shortened. When the addition amount reached 50%, it took only 31 seconds to complete the curing, and the curing rate increased by 50%, which could complete the rapid curing and film formation on the plate surface.
[0170] Fig.12 This is a photo of the photocurable water-based wood emulsion coatings prepared in Examples 7 to 12 applied twice on a wood surface. The paint film properties were tested, and the results are shown in Table 4.
[0171] Table 4
[0172]
[0173] As shown in Table 4, as the amount of Pickering emulsion added increases, the glossiness of the paint film formed by the composite emulsion gradually increases, the roughness gradually decreases, the pencil hardness tends to increase, and the adhesion of the emulsion is level 0, which can be well attached to the wood surface. When the amount of Pickering emulsion added is 50%, the performance of the paint film formed is optimal. At this time, the adhesion is level 0, the glossiness reaches 37.17, the roughness is reduced to 0.98μm, and the pencil hardness is 3H. Compared with the board coated with double-bond functionalized emulsion, all performances are improved. Compared with the paint film formed by one coating, the performance is also improved, which can meet the basic use needs.
Claims
1. A method for modularly assembling a light-curing water-based wood emulsion coating, characterized in that: The steps include: Step 1: Preparation of core-shell latex particles: S1: Prepare the following raw materials in parts by mass: 110-165 parts of deionized water, 50-80 parts of core monomer, 20-50 parts of shell monomer 1, 0.6-1.2 parts of grafting monomer, 6-12 parts of composite emulsifier, 0.2-0.5 parts of initiator and 0.3-0.6 parts of pH buffer; S2: dissolving 0.12-0.3 parts of initiator in 5.5-8 parts of deionized water to prepare a first initiator solution; dissolving 0.08-0.2 parts of initiator in 9.5-13 parts of deionized water to prepare a second initiator solution; S3: Mix the remaining deionized water, composite emulsifier and pH buffer, stir and pre-emulsify, then heat to 60°C, continue stirring for a certain period of time, add 8 to 12.8 parts of core layer monomer and first initiator solution, continue stirring for a certain period of time, then heat to 65°C, and when the reaction system solution turns milky blue and the reflux of the condenser disappears, a seed emulsion is obtained; S4: raising the temperature of the obtained seed emulsion to 80° C., reducing the stirring speed, dropping the remaining 42 to 67.2 parts of the core layer monomer into the seed emulsion, and adding the second initiator solution; S5: After the core layer monomer is added dropwise, the temperature is kept for a certain period of time, and the grafting monomer is added dropwise; after the grafting monomer is added, the shell layer monomer 1 is added dropwise immediately, and after the shell layer monomer 1 is fully added, the temperature is kept for a certain period of time, and the material is cooled to room temperature and discharged to obtain a core-shell latex particle emulsion; the core-shell latex particle emulsion is centrifuged and purified to collect the core-shell latex particles; Step 2: Assemble the Pickering emulsion: SⅠ: Prepare the following raw materials in parts by weight: 10-60 parts of deionized water, 10-50 parts of core-shell latex particles, 10-50 parts of photocurable oil phase reagent, 1-5 parts of photoinitiator, 0.5-1.2 parts of sodium magnesium lithium silicate, 0.16-0.32 parts of tannic acid and 1-5 parts of emulsifier; SⅡ: dissolving the emulsifier in deionized water to prepare an emulsion with a concentration of 1%, and dissolving tannic acid in the remaining deionized water to prepare a tannic acid solution; SⅢ: Add tannic acid solution to the core-shell latex particles, stir for 0.5-1.5h, then add sodium magnesium lithium silicate, vortex mix to ensure that the core-shell latex particles are tightly coated by the complex formed by tannic acid and sodium magnesium lithium silicate, centrifuge to remove excess complex, and obtain a functionalized emulsion; SⅣ: The obtained functionalized emulsion and the obtained emulsion are evenly mixed as the water phase, the photocurable oil phase reagent and the photoinitiator are evenly mixed as the oil phase, the oil phase is added dropwise to the water phase at a dispersion speed of 4000-6000 rpm, and the Pickering emulsion is assembled after sufficient dispersion to obtain a photocurable water-based wood emulsion coating.
2. The method for modularly assembling a light-curing waterborne wood emulsion coating according to claim 1, characterized in that: The core layer unit is vinyl acetate, the shell layer monomer 1 is styrene, the graft monomer is maleic anhydride, the composite emulsifier is an equal mass mixture of PCA507 and PCA078, the initiator is ammonium persulfate, the pH buffer is sodium bicarbonate, the photocurable oil phase reagent is a monomer or polymer containing acrylate double bonds, a monomer or polymer containing methacrylate double bonds, a monomer or polymer containing vinyl ether double bonds, a polymer containing allyl double bonds, a polymer containing other C=C double bonds or a double bond modified vegetable oil; the photoinitiator is 2-hydroxy-1-methylpropiophenone, and the emulsifier is sodium dodecyl sulfate, OP-10 or epoxy polyether polyol emulsifier.
3. The method for modularly assembling a light-curing waterborne wood emulsion coating according to claim 2, characterized in that: The monomer or polymer containing acrylate double bonds includes methyl acrylate, ethyl acrylate or acrylate type epoxy resin; the monomer or polymer containing methacrylate double bonds includes 2-methyl methacrylate, glycidyl methacrylate or polymethyl methacrylate; the monomer or polymer containing vinyl ether double bonds includes monovinyl ether, polyvinyl ether, vinyl ether type epoxy resin; the polymer containing allyl double bonds includes polyisoprene or allyl resin; the polymer containing other C=C double bonds includes alkyd resin; the double bond modified vegetable oil includes soybean oil, castor oil, linseed oil or tung oil modified with acrylate double bonds.
4. The method for modularly assembling a light-curing waterborne wood emulsion coating according to claim 3, characterized in that: The pre-emulsification temperature in step 1 S3 is 25-60°C, the stirring speed of the pre-emulsification is 200-600rpm, and the stirring time is 5-30min; after pre-emulsification, the temperature is raised to 60°C and the stirring time is continued for 10-35min, and the stirring time after adding the core layer monomer and the first initiator solution is continued for 10-40min.
5. The method for modularly assembling a light-curing waterborne wood emulsion coating according to claim 4, characterized in that: In step 1 S4, the stirring speed of the seed emulsion is 200-500 rpm, the dropping speed of the core layer monomer is 0.3-0.6 mL / min, and the second initiator solution is added 30 minutes after the core layer monomer is added, and the dropping speed is 0.1-0.3 mL / min.
6. The method for modularly assembling a light-curing waterborne wood emulsion coating according to claim 5, characterized in that: After the core layer monomer is added in step 1 S5, the insulation time is 5 to 30 minutes, the dripping speed of the grafted monomer is 0.5 to 3 mL / min, and the dripping speed of the shell layer monomer 1 is 0.5 to 2 mL / min. After dripping for 3 to 15 minutes, it is adjusted to 0.1 to 1 mL / min until all the shell layer monomer 1 is added. After all the shell layer monomer 1 is added, the insulation time is 20 to 40 minutes.
7. The method for modularly assembling a light-curing waterborne wood emulsion coating according to claim 6, characterized in that: In step 1 S5, after all the shell monomer 1 is added dropwise and kept warm for 30 minutes, the shell monomer 2 dipentene is added at a dropwise rate of 0.5 mL / min. After all the addition is completed, the mixture is kept warm for 30 minutes, cooled to room temperature and discharged to obtain a double-bond functionalized core-shell latex particle emulsion. The double-bond functionalized core-shell latex particles are collected after centrifugal purification.
8. A method for modularly assembling a light-curing waterborne wood emulsion coating according to any one of claims 1 to 7, characterized in that: The method further comprises the step 3 of preparing a photocurable composite emulsion: adding the Pickering emulsion assembled in the step 2 into the core-shell latex particle emulsion obtained in the step 1 and stirring evenly, and the obtained photocurable composite emulsion is the photocurable water-based wood emulsion coating.
9. The method for modularly assembling a light-curing waterborne wood emulsion coating according to claim 8, characterized in that: The mass ratio of the pickering emulsion assembled in step 2 to the core-shell latex particle emulsion obtained in step 1 is 1:9 to 5:
5.
10. A light-curing water-based wood emulsion coating prepared by the method for modular assembly of light-curing water-based wood emulsion coatings as claimed in any one of claims 1 to 9.